A mechanistic study of stratified patina evolution on Sn-bronze in chloride-rich atmospheres. (15th April 2020) - Chang, Tingru; Maltseva, Alina; Volovitch, Polina; Odnevall Wallinder, Inger; Leygraf, Christofer
Graphical abstract: Highlights: Patina stratification and flaking on Sn-bronze in Cl-rich atmospheric environments. Patina contains alternating Cu2 O and Cu2 (OH)3 Cl layers intercalated with Sn-oxides. Role of Cl and Sn in patina stratification is elucidated. Stratification is explained via redox reactions of soluble Sn-Cl and Cu-Cl complexes. Patina flaking is explained by molar volume changes during chemical transformation. Abstract: The complex stratified patina formed on Sn-bronze in chloride-rich atmospheres has been explored through long-term field exposures and short-term laboratory investigations using a multi-analytical approach. The stratified patina is composed of Cu2 O- and Cu2 (OH)3 Cl-rich sublayers intercalated by Sn-oxides, mainly SnO2 . The stratification is triggered by events of high chloride deposition, resulting in repeated dissolution and solidification of sublayers, whereby redox reactions between the intermediate products of Sn- and Cu-chlorides play a crucial role. Sn-induced patina stratification is a major reason for enhanced patina flaking on Sn-bronze and its accelerated corrosion rate compared to Cu metal in marine environments.